Advanced practice nursing roles in Arab countries in the Eastern Mediterranean region: a scoping review. Issue 5 (21st May 2022) - Almukhaini, Salma; Weeks, Lori E.; Macdonald, Marilyn; Martin-Misener, Ruth; Ismaili, Zeyana Al; Macdonald, Danielle; Al-Fahdi, Nora; Rasbi, Samira Al; Nasaif, Husain; Rothfus, Melissa A.
ABSTRACT: Objective: The objectives of this review were to map and summarize evidence regarding advanced practice nursing roles in Arab countries located in the Eastern Mediterranean region. Introduction: Many countries have reported an increase in the number and types of advanced practice nursing roles as research demonstrating their positive impact on patient and health system outcomes continues to accumulate. There is international evidence that the achievement of these outcomes depends on the effective implementation of advanced practice nursing roles at the organizational and country levels. A comprehensive review of the status of advanced practice nursing role implementation in Arab countries in the Eastern Mediterranean region has not been conducted. Inclusion criteria: Eligible studies included advanced practice nursing roles (including, but not limited to, nurse practitioners and clinical nurse specialists) in Arab countries in the Eastern Mediterranean region. Studies were considered if they focused on role development, titles, entry-level education, regulation and scope of practice, and facilitators and barriers to role implementation. Methods: A comprehensive systematic search was completed for both published and non-published literature. The databases searched included CINAHL, PubMed, PsycINFO, Embase, Nursing and Allied Health Database, and Scopus. Gray literature was searched using websites such as Google Scholar, ProQuest Dissertations and Theses, International Council of Nurses, World Health Organization regional office for the Eastern Mediterranean region, and websites of nursing associations and Ministries of Health in Arab countries. The search included literature published in Arabic and English from the inception of the databases to August 2020. Results: A total of 35 articles were included, the majority (n = 24) of which were published from 2010 onward. Ten of the included studies were empirical research papers that used qualitative and quantitative research designs. Advanced practice nursing role development is still in its infancy in most of the Arab countries in the Eastern Mediterranean region and can be described as slowly and steadily evolving. The main driving forces for the implementation of the roles in this region included a shortage of physicians both in number and specialties, the emergence of chronic diseases due to lifestyle changes, the desire to have more cost-effective primary care, and to advance nursing as a profession. Clinical nurse specialists and nurse practitioners are the most common titles for the advanced nursing roles practiced in the region. Some advanced practice nursing roles stipulated a master's degree as a minimum requirement, while others required a 12-month in-house training program. Oman is the only Arab country that authorizes nurse practitioners to prescribe pre-set medications. The common barriers to advanced practice nursing role implementation included a lack of recognition of roles at national levels, role ambiguity, lack of clear scope of practice, resistance from male physicians, low involvement of nurses in policy-making, and low status of nursing as a profession. Conclusion: The successful implementation and sustainment of advanced practice nursing roles in Arab countries in the Eastern Mediterranean region requires foundational work, including development of definitions, educational standards, regulations, and a clear scope of practice. Scoping review registration number: Open Science Framework: https://osf.io/wyj8a